Central venous catheters and complications - Nicpoń, Jakub; Karczmarek-Borowska, Bożenna; Pelc, Maria; Freygant, Krzysztof (European Journal of Clinical and Experimental Medicine, 2014)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Permanent venous line access is of a great importance in the treatment of oncological patients who are undergoing long-term chemotherapy. Modern medicine could not exist without a regular and reliable venous line access. In many departments central venous line (venous port systems), which allows a patient to move freely without fear of accidental removal of a catheter are used routinely. Venous port system consists of a reservoir compartment with a silicone membrane - septum, which can be repeatedly punctured, and a thin-walled intravascular catheter. A port is an undeniable convenience for patients and can fulfill its role for many months or even years. Especially in oncology the need to ensure permanent vascular line access is an essential part of the therapy due to severe irritation caused by many cytostatics. The aim of this study is to present the current standards and guidelines concerning intravenous port system and the most common early and late complications caused by the presence of central venous catheter. Based on a review of the bibliographical data, the authors presented the risk of common complications of central venous cannulation, the mechanism and the factors influencing the complications associated with the use of venous ports. Complications are an integral part of any medical treatment, therefore it is essential to understand their mechanism and learn appropriate methods of treatment and prevention. The use of ports is becoming increasingly popular in Polish oncology. Therefore, physicians should be familiar with advantages and common complications of the use of venous ports. Most of the complications result from the failure to comply with procedures, lack of adequate supervision, negligence or simply insufficient knowledge.